Load-Velocity Relationships of the Back vs. Front Squat Exercises in Resistance-Trained Men. Issue 2 (February 2019) - Spitz, Robert W.; Gonzalez, Adam M.; Ghigiarelli, Jamie J.; Sell, Katie M.; Mangine, Gerald T.
Abstract : Abstract: Spitz, RW, Gonzalez, AM, Ghigiarelli, JJ, Sell, KM, and Mangine, GT. Load-velocity relationships of the back vs. front squat exercises in resistance-trained men. J Strength Cond Res 33(2): 301–306, 2019—The purpose of this investigation was to describe and compare changes in barbell velocity in relation to relative load increases during the back squat (BS) and front squat (FS) exercises. Eleven National Collegiate Athletic Association Division I baseball position players (19.4 ± 1.0 years; 182.4 ± 6.5 cm; and 87.2 ± 7.4 kg) performed trials at maximum speed with loads of 30, 50, 70, and 90% of their predetermined 1 repetition maximum (1RM) for both BS and FS. Peak and mean velocity was recorded during each repetition using an accelerometer. Differences between exercises and relative loading were assessed by separate 2 × 4 (condition × relative load) repeated-measures analysis of variance for mean and peak velocity. In addition, the load-velocity relationship across submaximal loadings in BS and FS were further assessed by calculating their respective slopes and comparing slopes through a paired-samples t -test. No significant condition × relative load interactions were noted for mean velocity ( p = 0.072) or peak velocity ( p = 0.203). Likewise, no significant differences in the slope for BS and FS were noted for mean velocity ( p = 0.057) or peak velocity ( p = 0.196). However, significant main effects for relative load were noted for both mean and peak velocity ( p < 0.001), whereby mean and peak velocity were progressively reduced across all relative loads (i.e., 30, 50, 70, and 90% 1RM) for both the BS and FS. Our results demonstrate that the load-velocity relationships of the BS and FS exercises seem to be similar; therefore, similar approaches may be used with these squat variations when monitoring barbell velocity or implementing velocity-based strength training.